Mortality and Adverse Outcomes in Patients of Morbidly Adherent Placenta - Rabbani, Attia; Khudija, Aysha; ., Heema; Ghafoor, Saira; Aftab, Shazia; Ali, Nazish (Annals of Punjab Medical College, 2019)
Objective: To determine the mortality and adverse outcomes in cases presenting with morbidly adherent placenta presenting to a tertiary care hospital. Study design: This was a cross sectional study. Settings: District Headquarter Hospital Rawalpindi. Duration: 01-06-2015 to 30-11-2015. Methodology: The females between the age of 20 to 40 years, delivering at the same institute with morbidly adherent placenta were selected. The diagnosis of MAP was made on the basis of clinical or histo-pathological examination. These cases then underwent with hysterectomy and were looked for bladder injury, blood loss, ICU admission or maternal death. Results: In the present study 40 cases of morbidly adherent placenta were included. the mean age of the subjects was 33.58±6.34 years. The mean parity was 2.1±0.98 and 54% of the cases had a prior C section and only 18% of the cases had a regular ante natal follow up. After the surgery bladder injury was seen in 10%, ICU admission in 32.50% of the cases and mortality in 30% of the cases while average blood loss was 2.8±0.78 litres. Conclusion: Morbidly adherent placenta is a highly morbid condition where it can be fatal in almost 1/3rd of the cases.